Checklist for Change : Making American Higher Education a Sustainable Enterprise - Zemsky, Robert, 1940- (Book collections on Project MUSE., 2013)
This book diagnoses the problems in American higher education in the 2010s and describes principal reforms that must occur in combination in order for it to remain a vital enterprise: a fundamental recasting of federal financial aid; new mechanisms for better channeling the competition among colleges and universities; recasting the undergraduate curriculum; and a stronger, more collective faculty voice in governance that defines not why, but how the enterprise must change.